Editorial Advisory Board - Kalaitzi, Dimitra (My University, 2026)
International Journal of Logistics (IJoL) publishes original and challenging work that has a clear applicability to the business world. High quality contributions are therefore welcomed from both academics and professionals working in the field of logistics and supply chain management. https://www.tandfonline.com/journals/cjol20/about-this-journal#aims-and-scope